Book selection: an introduction to principies and practice, de David Spiller (Revista de Biblioteconomia de Brasília, 1975)
SPILLER, David. Book selection: an introduction to principles and pratice. 2. ed. rev. London: Clive Bingley, 1974. 142 p.